2018
DOI: 10.1016/j.socscimed.2017.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of the impact of economic empowerment on risk for intimate partner violence among married women in rural Maharashtra, India

Abstract: The purpose of this study was to assess via longitudinal analysis whether women's economic empowerment and financial inclusion predicts incident IPV. This prospective study involved analysis of three waves of survey data collected from rural young married women (n = 853 women) in Maharashtra at baseline and 9&18 month follow-ups. This study, which was in the field from 2012 to 2014, was conducted as part of a larger family planning evaluation study unrelated to economic empowerment. Participants were surveyed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 34 publications
6
31
0
2
Order By: Relevance
“…Second part collected the information for social, economic, and political women empowerment. The items of political empowerment were adapted from Niemi, Craig, and Mattei (1991) and Boley, Ayscue, Maruyama, and Woosnam (2016); the items of social empowerment were adapted from Basu (2006) and Boley et al (2016); and the items of economic empowerment were adapted from Raj et al (2018), Postmus et al (2013) and Basu (2006). All estimations in the investigation were subjective assessments of the respondents utilizing five-point Likert scale (where 1 represents strongly disagree and 5 represents strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…Second part collected the information for social, economic, and political women empowerment. The items of political empowerment were adapted from Niemi, Craig, and Mattei (1991) and Boley, Ayscue, Maruyama, and Woosnam (2016); the items of social empowerment were adapted from Basu (2006) and Boley et al (2016); and the items of economic empowerment were adapted from Raj et al (2018), Postmus et al (2013) and Basu (2006). All estimations in the investigation were subjective assessments of the respondents utilizing five-point Likert scale (where 1 represents strongly disagree and 5 represents strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, evaluation studies have also shown that such interventions do not necessarily result in decreases in women's experience of IPV. There are mixed study results from different contexts demonstrating increases and decreases in IPV that warrant further exploration (Dalal et al, 2013;Raj et al, 2018;Vyas & Watts, 2009). Theoretically, women's empowerment has the potential to have a positive or negative impact on their IPV risk; women with education, who contribute to household finances or have control over resources, may have higher household status and be less vulnerable to IPV (Vyas & Watts, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Women's reproductive empowerment is defined as the ability and the right to decide freely on reproductive activities such as the number of children, childbearing time, and the age gap between the children. Adequate women's reproductive empowerment benefits the entire families and improves the productivity of future generations (8)(9)(10). Further, it improves women's self-confidence in childbearing and managing birth intervals (11).…”
Section: Introductionmentioning
confidence: 99%